Effects of periodontitis on cancer outcomes in the era of immunotherapy - Pai, Sara I; Matheus, Henrique R [UNESP]; Guastaldi, Fernando P S (Elsevier, 2023)
Periodontitis results from dysbiosis of the oral microbiome and affects up to 70% of US adults aged 65 years and older. More than 50 systemic inflammatory disorders and comorbidities are associated with periodontitis, many of which overlap with immunotherapy-associated toxicities. Despite the increasing use of immunotherapy for the treatment of cancer, uncertainty remains as to whether the microbial shift associated with periodontal disease can influence response rates and tolerance to cancer immunotherapy. We herein review the pathophysiology of periodontitis and the local and systemic inflammatory conditions related to oral dysbiosis, and discuss the overlapping adverse profiles of periodontitis and immunotherapy. The effects of the presence of Porphyromonas gingivalis, a key pathogen in periodontitis, highlight how the oral microbiome can affect the hosts’ systemic immune responses, and further research into the local and systemic influence of other microorganisms causing periodontal disease is necessary. Addressing periodontitis in an ageing population of people with cancer could have potential implications for the clinical response to (and tolerability of) immunotherapy and warrants further investigation.